Some of the features of mastering word semantics while learning the second language - Jacikevičius, A. (Psichologija, 1966)
This article summarizes the research on memory of word semantics of the second language (Russian) in Lithuanian university and secondary school students. Experimental results show that subjective word semantics recorded in memory does not match the objective word semantics of the same words. Two-language “vocabularies” in students’ memory differs significantly from usual printed modelled vocabularies. Semantic formation peculiarities in second language show that in the process of learning the new language it is important to devote more effort in establishing the relations between signs and meanings.